Islamic Work Ethics: A Thematic Commentary Study - Miftah Khilmi Hidayatulloh (Cakrawala: Jurnal Studi Islam, 2019)
Veysel Bozkurt's research proved that Protestant ethics, which consists of work ethic and asceticism did not just occur to Protestant Christians. However, it also occurred in Turkish and Kyrgyz communities where the majority of the population is Muslim. Researcher reinforce Veysel Bozkurt's theory by revealing the work ethic and asceticism in the Qur'an with a thematic commentary approach. This research found that the Qur'an teaches four work ethics and two attitudes of asceticism. The four-work ethics are that work is obligatory, work must be optimal beyond basic needs, work is jihad, and work must be based on the principle of goodness. While the two attitudes of asceticism are strong spiritual and managing wealth wisely